Modeling the action of anaerobic biofilm - Poliakov, V.L. (Доповіді НАН України, 2021)
A mathematical problem of the action of a representative biofilm in the absence of oxygen is formulated. The
anaerobic process of decomposition of a dissolved organic matter is considered as a two-stage process, proceeding
due to the vital activity of two groups of microorganisms. An approximate analytic solution allowing one to calculate
the concentration and consumption of primary and secondary organic substrates with minimal errors has been
obtained. On test examples, their rates of transfer through the biofilm surface are determined, and the possibility
of the movement of volatile fatty acids in both directions is discussed. Сформульовано математичну задачу дії репрезентативної біоплівки за відсутності кисню. Анаеробний
процес розкладу розчиненої органіки розглядається як двостадійний, який протікає завдяки життєдіяльності двох груп мікроорганізмів. Одержано наближений аналітичний розв’язок, що дозволяє з мінімальними похибками розраховувати концентрації і витрати первинного і вторинного органічних субстратів.
На тестових прикладах визначено їх витрати через поверхню біоплівки і демонструється реальність руху
летючих кислот в обох напрямках.